A New Mechanism of Silicone Oil-Induced Glaucoma and Its Management. (2nd June 2022) - Kumar, Harsh; Talwar, Dinesh; Thulasidas, Mithun; Taneja, Surbi
Abstract : Purpose . To describe a case of secondary acute angle closure glaucoma due to silicone oil migration into the posterior chamber causing entrapment of aqueous and its successful management. Case Presentation . A 69-year-old female presented with decreased vision and pain in the left eye (LE) for one month. She had a history of complicated phacoemulsification with nucleus drop and retinal detachment in LE, for which vitreoretinal surgery with silicone oil endotamponade was done. She was also a known case of primary open angle glaucoma on medications. The corrected distance visual acuity was 20/20 and 20/125 in the right eye (RE) and LE, respectively. The intraocular pressure (IOP) was 18 mmHg in RE and 45 mmHg in LE. Anterior segment examination of LE revealed 270° of iridocorneal apposition in the periphery of the anterior chamber. Fundus examination of LE showed silicone oil filled vitreous cavity with attached retina. Given the recent history of silicone oil injection and elevated IOP despite maximum antiglaucoma medications, we decided to perform laser peripheral iridotomy (LPI) in the area of iridocorneal apposition. Following LPI, the IOP in LE came down to 17 mmHg and remained stable within the normal range for one month, after which the patient was taken up for silicone oil removal. Conclusion . This case report highlights a new mechanism of silicone oil-induced glaucoma and the technique of performing LPI in the area of iridocorneal apposition, for the first time in the literature. Silicone oil migration into the posterior chamber from the vitreous cavity in the presence of zonular dehiscence can push the iris forward and lead to iridocorneal apposition, resulting in an acute rise in IOP. Performing LPI within the area of iridocorneal apposition can help the aqueous seep into the anterior chamber and release the silicone oil globule trapped behind the iris to enter the anterior chamber, thus relieving the iridocorneal adhesions and lowering the IOP.